Formulasi dan Evaluasi Tablet Hisap Ekstrak Elderberry (Sambucus nigra L.) menggunakan Metode Granulasi Kering - Sulistiani, Ine; Gitalis Kustiawan, Mayas; Qiroatul Fatihah, Naila; Friza Puspita, Nazwa; Rosita, Nur; Puspa Sari, Pungki; Ahista Qolbi, Raihan; Azzahra, RD Salma; Sugiharti Murni, Resha; Puspita Tanjung, Yenni (Jurnal Medika Farmaka, 2025)
Elderberry fruit (Sambucus nigra L.) is known to contain flavonoids, anthocyanins, vitamin C and hasantioxidant activity that has the potential to increase immunity and help relieve symptoms of upper respiratorytract infections. This study aims to formulate elderberry extract-based lozenges. The lozenges were formulatedusing the dry granulation method with variations in amprotab concentration to see its effect on tablet quality.Evaluation was carried out on the physical properties of the granules and the physical quality of the resultingtablets. The results showed that formula F2 (amprotab 16.67%) showed the characteristics closest to optimal.The evaluation of the granules had a flow rate of 18.16 g/second, an angle of repose of 20.44°, acompressibility of 10.49%, and a hausner ratio of 1.11, which means it showed good flow properties. Thetablets of this formula have a disintegration time of 9 minutes 16 seconds, friability of 0.92%, hardness of 4.5kg, average weight of 602 mg, diameter of 1.21 cm, and thickness of 0.525 cm. Parameters as uniformity ofweight and hardness of the tablets do not meet the Pharmacopoeia standards. Therefore, further optimization isneeded in the molding process and adjustment of the excipient ratio to obtain lozenges with consistent qualityand according to standards. In conclusion, the formulation of lozenges with elderberry powder has the prospectto be further developed, with formulation optimization to improve the quality of the tablets to meet all qualitystandards.Keywords: amprotab, mannitol, elderberry extract, lozenge